Space-Time Block Coding with Beamforming for Triple-Polarized Uniform Linear Array Systems - Xin Su; Kyung Hi Chang (International Journal of Antennas and Propagation)
Generally, space-time block coding (STBC) and beamforming (BF) gains cannot be obtained simultaneously because the former performs well under a low correlated MIMO channel, and the latter works efficiently in an environment with high correlation. However, array systems with antenna polarization have the potential to achieve gains with both techniques simultaneously because the cross-branch links in the system are usually uncorrelated. The cross-array links, on the other hand, can be highly correlated by setting the array element space equal to, or less than, a half-wavelength. This paper proposes a scheme to explore STBC and BF simultaneously via a triple-polarized uniform linear array (TPULA) system. The proposed scheme was verified based on the Long Term Evolution-Advanced (LTE-A) specification under a polarized MIMO (PMIMO) channel model, and therewith, the simulation results confirmed the validity of our proposed scheme.